KECEMASAN ORANGTUA TERHADAP MASA DEPAN ANAK PENYANDANG DISABILITAS INTELEKTUAL DI SLB C BINA ASIH CIANJUR - Mutiara Febya Insani; Aep Rusmana; Zaenal Hakim (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
This study aims to obtain an empirical overview of the characteristics and anxiety of parents about the future of children with intellectual disabilities in SLB C Bina Asih Cianjur, which includes emotional reactions, cognitive reactions, and physiological/physical reactions. Research used the quantitative approach with descriptive research methods. The population are 83, to determine the sample, researcher used incidental sampling to obtain 55 respondents. Data was obtained through questionnaire according to the HRS-A that has been adapted and documentation studies. The researcher tested the validity of the measuring instrument used face validity. The results were presented by frequency distribution tables. Data analysis techniques using quantitative with descriptive statistics, then determine the score of respondents with the most frequency (mode). The results showed the overall level of respondents anxiety were in medium category with the most score 61. Score variations include emotional reactions were in the medium category with the score of 28, cognitive reactions were in the medium category with the score of 21, and physiological reactions were in the mild category with the score of 10. Several factors that cause anxiety conditions of parents include narrow perceptions, unpleasant experiences, and pessimism about the ability of children with intellectual disabilities. Based on the results analysis, there needs an effort to reduce anxiety of parents and increase their insight related to anxiety about the future of their children. The researcher recommends “Self Help Group for Parents of Children With Intellectual Disabilities” program . The method used social group work with self help group types.